Improving the Ability to Read Q.S Al-Ma'un Through the Listening Team Strategy in Students at SD Negeri 100506 Tapusnabolak - Lubis, Hotmida; Wardana, Ali; Efendi, Herman; Rasmi; Sari, Dera (MANDAILING GLOBAL EDUKASIA, 2025)
The main problem in this study is how to improve the ability to read Q.S al-Ma'un through the listening team strategy in grade V students of SD Negeri 10506 Tapusnabolak with Classroom Action Research (CAR). The limitation of the problem in the discussion discussed is how to improve the ability to read Q.S al-Ma'un through the listening team strategy in SD Negeri 100506 Tapusnabolak. The purpose of this study is to explain how to improve student learning outcomes in reading Q.S al-Ma'un in the subject of Islamic Religious Education for grade V at SD Negeri 100506 Tapusnabolak. In this discussion the author uses the classroom action research method. CAR is a research activity that seeks to improve the quality of the process and learning outcomes through a cyclical action based on the teacher's in-depth observation of the problems that occur and believes that they will get the best solution for students in their own classroom environment. Cycle I, students who have not completed or have not reached the KKM are 33.33% while students who have completed their studies are 66.66%. The average student learning outcomes in cycle I were 77.5%. Based on the test results, in cycle I, the success of the research has not been achieved because students who have reached the minimum completion level set ≤ 80%. In cycle II, students have achieved 91.66% learning completion. The average student learning outcomes in cycle II have reached 83.66. This shows that Islamic Religious Education using the Listening Team Strategy has been successful because the minimum completion level of student achievement is 80%. Listening Team Strategy